Clinicopathologic Features of Low-grade Appendiceal Mucinous Neoplasm: A Single-institution Experience of 117 Cases. (November 2020) - Bell, Phoenix D.; Huber, Aaron R.; Drage, Michael G.; Barron, Samuel L.; Findeis-Hosey, Jennifer J.; Gonzalez, Raul S.
Abstract : Low-grade appendiceal mucinous neoplasm (LAMN) is an enigmatic tumor that lacks the capacity for classic invasion but can dissect through the appendiceal wall, causing pseudomyxoma peritonei (PMP). Most large studies of the histologic spectrum of LAMN and its rate of associated PMP include cases submitted from outside institutions, potentially skewing their findings. We identified 117 cases of LAMN at our institution. Hematoxylin and eosin-stained slides from each were reviewed, and clinical and pathologic parameters were noted. The patients were 76 females and 41 males, with a mean age of 60 years. Presenting symptoms were available for 113 patients; the majority (56%) were symptomatic, typically with abdominal pain. Ninety-one tumors (78%) were grossly dilated, and the entire appendix was submitted in 88 (75%) cases. Median lesion size was 5.5 cm. Ninety-two cases (79%) demonstrated epithelial denudation; these were often markedly dilated and contained intraluminal or mural microcalcifications. Thirty-two (27%) had a mucosal Schwann cell proliferation. On the basis of the American Joint Committee on Staging eighth edition cancer staging manual, of 117 cases, 66% were staged as pTis, 9% as pT3, 24% as pT4a, and 2% as pT4b. Ten cases (9%) were associated with histopathologic evidence of disseminated PMP. Only 1 patient died of disease, while 3 were alive with disease at last follow-up. Previous LAMN studies have utilized both departmental and extradepartmental material; our single-institution review demonstrated lower rates of PMP than some prior studies. Some LAMNs may be markedly dilated with extensive denudation, making the diagnosis difficult to confirm microscopically and ultimately requiring submission of the entire appendix for histologic evaluation.